2023
DOI: 10.1371/journal.pone.0294531
|View full text |Cite
|
Sign up to set email alerts
|

Altruism and anti-anthropocentrism shape individual choice intentions for pro-environmental and ethical meat credence attributes

Sven Anders,
Marina Malzoni,
Henry An

Abstract: Food consumption patterns are changing as consumers are becoming more aware and interested in sustainable and ethical food production practices. The growing disconnect between primary (livestock) agriculture and society reinforces the importance of research examining the motivations behind consumer purchase behaviors. However, evidence that links latent consumer psychometric factors and observed heterogeneity in concerns for agriculture to individual food purchase intentions remains scarce. We employ large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…Indeed, only a few studies reported significant differences, but with contrasting results regarding the higher or lower circulation of different pathogens under the different types of management. As anticipated in the introduction, the overall interpretation of our results suggest that CvsO and IvsE comparisons can be regarded as partially equivalent in some respects, for example in relation to the consumers' perception of issues such as animal welfare and sustainability (e.g., Harper and Makatouni, 2002;Anders et al, 2023;Clark et al, 2024). Therefore, the main outcome of our study, in relation to the public debate on the "pros" and "cons" of the different types of animal management, suggests that organic and extensive farming is not correlated with a decrease of circulation of infectious agents, compared to conventional and intensive dairy FMS.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, only a few studies reported significant differences, but with contrasting results regarding the higher or lower circulation of different pathogens under the different types of management. As anticipated in the introduction, the overall interpretation of our results suggest that CvsO and IvsE comparisons can be regarded as partially equivalent in some respects, for example in relation to the consumers' perception of issues such as animal welfare and sustainability (e.g., Harper and Makatouni, 2002;Anders et al, 2023;Clark et al, 2024). Therefore, the main outcome of our study, in relation to the public debate on the "pros" and "cons" of the different types of animal management, suggests that organic and extensive farming is not correlated with a decrease of circulation of infectious agents, compared to conventional and intensive dairy FMS.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, only a few studies reported significant differences, but with contrasting results regarding the higher or lower circulation of different pathogens under the different types of management. As anticipated in the introduction, the overall interpretation of our results suggest that CvsO and IvsE comparisons can be regarded as partially equivalent in some respects, for example in relation to the consumers' perception of issues such as animal welfare and sustainability (e.g., Harper and Makatouni, 2002;Anders et al, 2023;Clark et al, 2024). Therefore, the main outcome of our study, in relation to the public debate on the "pros" and "cons" of the different types of animal management, suggests that organic and extensive farming is not correlated with a decrease of circulation of infectious agents, compared to conventional and intensive dairy FMS.…”
Section: Discussionsupporting
confidence: 72%